Pre-injury use of antiplatelet and anticoagulations therapy are associated with increased mortality in a cohort of 1038 hip fracture patients. Issue 6 (June 2021) - Mahmood, Aatif; Thornton, Luke; Whittam, David G.; Maskell, Perry; Hawkes, David H.; Harrison, William J.
Highlights: pre-injury antiplatelet therapy is a strong indicator for high risk patients with higher expected mortality after hip fracture surgery. no evidence to support delayed surgery in patients taking DOACs. Patients on anticoagulants donot have a higher wound complication rate. Abstract: Background: Hip fractures are a large burden on the health care systems of developed nations. Patients usually have multiple co-morbidities and the pre-injury use of anticoagulants and anti-platelet medication is common. Materials and methods: This study used a single hospital hip fracture database to facilitate a retrospective analysis of the impact of anti-coagulation and anti-platelet therapy on mortality and complications after surgical management of hip fractures. There were 92 patients on warfarin, 69 on DOAC, 260 antiplatelet patients and 617 control patients. Results: Mortality rates at 30 days were 4.8% for the control group, 12.6% for the antiplatelet group, warfarin 7.0%, 9.5% for Direct Oral Anticoagulant (DOAC) group, p = 0.004. Mortality rates at 1 year were 22.4% for the control group, 32.3% for the antiplatelet group, 29.3% for the warfarin group and 29.0% for DOAC group (p=0.007). Amongst complications, significant differences were found in transfusion (DOAC) and wound ooze (warfarin) rates, but the study did not detect significant clinical consequences arising from these differences. A matched analysis for age, sex, and ASA was undertaken to look in more detail at mortality data. Some mortality differences remained between groups with anti-platelet medication associated with increased mortality, but the differences no longer appeared to be significant. Our data suggests that this is a non-causal association, which could be incorporated into predictive mortality risk scores such as the Nottingham hip fracture score. Conclusion: We believe that pre-injury antiplatelet therapy is a strong indicator for high risk patients with higher expected mortality after hip fracture surgery. We saw no evidence to support delayed surgery in patients taking DOACs